This is a repeated question: Language Logic and Proof Q. 6.26
Using the natural deduction rules, give a formal proof of
A ∨ D
from the premises
- A ∨ (B ∧ C)
- (¬ B ∨ ¬ C) ∨ D
The LPL textbook has not yet introduced material implication or the implies "-->" symbol and the answer given in the above link does NOT satisfy the question in the book and I was surprised the user accepted the answer as appropriate.
The answer is valid until step 22, since the textbook has not introduced those forms of steps. Is there a way to use this proof and using other rules to show the implication that ~A --> D and A --> ~D therefore A V D ?
How would I go about solving this proof in Fitch without --> or material implication?
Rules you can use:
V intro, elim (disjunction)
^ intro, elim (conjunction)
~ intro, elim (negation)
= intro, elim